Facile Syntheses of Anthra[2,3-b]chalcogenophenes - Niimi, Kazuki; Miyazaki, Eigo; Osaka, Itaru; Takimiya, Kazuo (Synthesis, 2012)
A simple and straightforward method for the synthesis of anthra[2,3-b]furan, anthra[2,3-b]thiophene, and anthra[2,3-b]selenophene from readily available 2-methoxyanthracene is described.
Keywords: anthracene; heteroannulation; oxygen; sulfur; selenium